The Silent Voices of Disabled Girls in Yazd City: Understanding Limitations and Deprivations - Mahnaz Farahmand; Fatemeh Azizi Nezhadfard (جامعه شناسی کاربردی)
IntroductionGirls with physical and motor disabilities represent one of the most vulnerable groups in contemporary society, possessing distinct needs and challenges compared to other segments of the population (Naghdi et al., 2023). Their disabilities are often subject to societal judgment, which can exacerbate their struggles (Blandul, 2024). This complex reality is further compounded by intersections with gender, class, poverty, and other social, cultural, political, and economic factors that shape their experiences (Amjad et al., 2023). Disability incurs significant social and health costs for these girls, leading to heightened stress and vulnerability (Schofield et al., 2024). As a result, disabled girls frequently become targets of stereotypes and discriminatory attitudes. This research aimed to explore the experiences and perspectives of disabled girls in Yazd City, addressing these questions: What experiences and mentalities does disability bring to these girls? How do they perceive, feel, and reinterpret disability within the contexts of family and society?  Materials & MethodsThis study utilized a qualitative approach grounded in interpretive phenomenology based on the method developed by Dikelman et al. (1989). The participants were girls with physical and motor disabilities from Yazd City with a total of 18 individuals selected through purposive and theoretical sampling techniques. Data were collected through in-depth, semi-structured interviews, which were recorded with the participants' consent. After conducting the interviews and transcribing the conversations, the data were analyzed using Dikelman's analytical method. The interview locations were chosen for the comfort of the participants. To ensure the quality and reliability of the data, the researchers collected multiple pieces of information and direct quotes. A key ethical consideration was obtaining informed consent from both the participants and their parents, with interviews conducted only as long as the participants were comfortable. The data collection process spanned 9 months. Discussion of Results & ConclusionThis article examined the experiences and perspectives of disabled girls through a qualitative lens. During the coding process, themes, such as identity stigma, leadership, marriage anxiety, forced confinement at home, educational challenges, inequality, and social restrictions emerged. The participants expressed that their disability was not the sole source of their difficulties; rather, it was the attitudes of family, peers, and society that had contributed to and exacerbated these challenges, creating a vicious cycle of limitations and exclusion. The girls reported that their families influenced by traditional and stereotypical beliefs feared social judgment and were often resistant to their pursuit of education, employment, and marriage. They perceived disability as a debilitating factor, instilling in them a sense of futility regarding their efforts. The belief that their movement difficulties and gender would render their aspirations fruitless further compounded their challenges.Participants noted that their limited mobility had prevented them from engaging in social situations. The absence of accessible facilities, such as ramps and elevators, along with inadequate transportation options and high travel costs, had created significant barriers to attending schools, universities, and workplaces. They highlighted that the partial implementation of laws and the lack of medical, educational, and employment support in organizational policies had led to their social exclusion. Moreover, the difficulties in commuting coupled with the meaningful stares, labels, and judgments from others had contributed to feelings of loneliness, depression, and a sense of being trapped at home.